Evaluating Homestay Management Training Using the Kirkpatrick Model in Kuta Village, SEZ Mandalika-Indonesia - Rizal Kurniansah; Masrun; Adhitya Bagus Singandaru; Siti Hamdiah Rojabi (Lembaga Publikasi Ilmiah Nusantara, 2026)
The development of community-based tourism increasingly relies on training programs to enhance local capacity; however, their effectiveness often remains limited to short-term learning outcomes. This study evaluates the effectiveness of homestay management training in Kuta Village, Mandalika Special Economic Zone, by addressing the gap between learning outcomes and business performance. Using a convergent mixed-methods design based on the Kirkpatrick Model, quantitative data were collected from 50 homestay managers through Likert-scale questionnaires, complemented by in-depth interviews with 15 key stakeholders. The results show high participant satisfaction (Level 1) and strong learning outcomes (Level 2), with 66%–70% of respondents rating training on guest service, room cleanliness, and food management as effective to highly effective. However, effectiveness declines in strategic competencies, with only 42% reporting effectiveness in digital marketing and 34% in foreign language skills. At the behavioral level (Level 3), improvements are evident in service and cleanliness practices, but remain inconsistent in business management and in digital marketing adoption, with 52% of respondents still facing difficulties with digital promotion. At the results level (Level 4), training contributes to improved service quality and homestay image. Nevertheless, its impact on occupancy and income remains moderate, as 48% of respondents report constraints related to infrastructure and capital. This study offers a novel contribution by empirically demonstrating the training transfer gap (Level 2 to Level 3) in community-based homestay contexts within a super-priority tourism destination. It extends the Kirkpatrick Model by integrating structural constraints into training evaluation. Practically, the findings highlight the need to combine training with continuous mentoring and institutional support to achieve sustainable tourism outcomes.